SHARIA ECONOMIC ISSUES IN THE PERSPECTIVE OF M. DAWAM RAHARDJO - Puspita, Adinda Novelia; Syah, Toufan Aldian (AJIRSS: Asian Journal of Innovative Research in Social Science, 2022)
This study aims to study further the thoughts of a Muslim figure in Indonesia who has a different view of the Islamic economic system. He is M. Dawam Rahardjo, whose thoughts give rise to many controversies. One of them is to disagree with the bank's interest ban. The method used in this study is literature studies. The results showed that according to M. Dawam Raharjo, which is forbidden in the Qur'an as the holy book of Muslims is transacting in a bathil. Financial transactions conducted at financial institutions are most profitable for all parties